Complications of tattoos and permanent makeup: overview and analysis of 308 cases. (3rd October 2021) - van der Bent, S.A.S.; Rauwerdink, D.; Oyen, E.M.M.; Maijer, K.I.; Rustemeyer, T.; Wolkerstorfer, A.
Abstract: Background: Worldwide 10–20% of the population is tattooed. However, tattoo complications can occur, such as allergic tattoo reactions, infections, and manifestations of autoimmune dermatoses. Despite the growing popularity of tattoos and changes in tattoo ink composition over the last decades, little is known about these complications, its clinical aspects, pathomechanism, and relative occurrence. Objective: The aim of this article is to describe the types and clinical aspects of dermatological tattoo complications, its relative occurrence and underlying conditions. Methods: We performed a retrospective cohort study enrolling all patients with tattoo complications from the Tattoo Clinic. Tattoo complications were categorized into infections, inflammatory tattoo reactions, neoplasms, or miscellaneous reactions and correlated to clinical data. Results: Of the total of 326 patients, 301 patients were included with 308 complications. The majority of the complications were chronic: 91.9%. Allergic red tattoo reactions and chronic inflammatory black tattoo reactions (CIBTR) accounted for 50.2% and 18.2%, respectively, of all tattoo complications. Of these CIBTR reactions, extracutaneous involvement was found in 21.4%, including tattoo‐associated uveitis (7.1%) and systemic sarcoidosis (14.2%). Of all black tattoo reactions, systemic sarcoidosis was found in 7.8%. Conclusion: Tattoos can cause a wide range in complications that may start years after getting the tattoo. The most frequent tattoo reactions are allergic red tattoo reactions and chronic inflammatory black tattoo reactions, making these the most relevant for the dermatologist. CIBTR have a high percentage of multi‐organ involvement, and therefore, screening for sarcoidosis, including ocular involvement, is advised.